JNK and NADPH Oxidase Involved in Fluoride-Induced Oxidative Stress in BV-2 Microglia Cells - Ling Yan; Shengnan Liu; Chen Wang; Fei Wang; Yingli Song; Nan Yan; Shuhua Xi; Ziyou Liu; Guifan Sun (Mediators of Inflammation)
Excessive fluoride may cause central nervous system (CNS) dysfunction, and oxidative stress is a recognized mode of action of fluoride toxicity. In CNS, activated microglial cells can release more reactive oxygen species (ROS), and NADPH oxidase (NOX) is the major enzyme for the production of extracellular superoxide in microglia. ROS have been characterized as an important secondary messenger and modulator for various mammalian intracellular signaling pathways, including the MAPK pathways. In this study we examined ROS production and TNF-α, IL-1β inflammatory cytokines releasing, and the expression of MAPKs in BV-2 microglia cells treated with fluoride. We found that fluoride increased JNK phosphorylation level of BV-2 cells and pretreatment with JNK inhibitor SP600125 markedly reduced the levels of intracellular and NO. NOX inhibitor apocynin and iNOS inhibitor SMT dramatically decreased NaF-induced ROS and NO generations, respectively. Antioxidant melatonin (MEL) resulted in a reduction in JNK phosphorylation in fluoride-stimulated BV-2 microglia. The results confirmed that NOX and iNOS played an important role in fluoride inducing oxidative stress and NO production and JNK took part in the oxidative stress induced by fluoride and meanwhile also could be activated by ROS in fluoride-treated BV-2 cells.